THE RELATIONSHIP OF FAMILY HARMONY TO STUDENT LEARNING OUTCOMES SDN 060929 MEDAN JOHOR - Yola Sundari; Zon Saroha Ritonga (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2020)
This study aims to determine the relationship between family harmony and student learning outcomes. The hypothesis in this study is that there is a relationship between family harmony and student learning outcomes. This research was conducted at SD Negeri 060929 Medan Johor with a population of 72 and a sample of 23 students. This type of research is quantitative with the correlation method. This type of research is to see the relationship between one or several variables with other variables. Data collection techniques used are questionnaires and documentation. Data collection was carried out using a family harmony scale made with a Likert scale model as well as reports on student learning outcomes in the form of scores obtained by students in the second semester. The reliability of the family harmony scale was tested using the Cronbach Alpha reliability coefficient method and the results obtained were 0.816. Based on the Pearson Product Moment correlation analysis, the correlation coefficient was 0.833 with a significance level of 0.413. This shows that there is a very strong relationship between family harmony and student learning outcomes.